Contribution of Metal Species to the Heterogeneous Photocatalytic Degradation of Natural Organic Matter - Ceyda Senem Uyguner; Miray Bekbolet (International Journal of Photoenergy)
The role of organic matters which are high molecular weight macromolecules in natural water supplies and their subsequent removal by advanced oxidation technologies has gained importance because they posses a substantial capacity to complex dissolved metal species. The present study was conducted to evaluate the impact of aqueous Cr(VI) and Mn(II) species on the photocatalytic oxidation of humic acids as a major component of natural organic matter in aquatic systems. The photocatalytic decolorization rate of humic acid was followed by pseudo-first-order and Langmuir Hinshelwood kinetic models. The presence of aqueous Cr(VI) and Mn(II) species did not significantly alter the degradation efficiency (≤20%) in terms of first-order kinetic model. Although the impact of manganese species could be considered as insignificant, a substantial adsorption effect could be assessed as reflected by respective Langmuir-Hinshelwood kinetic model parameters.